CONSTITUTIONAL AMENDMENT NO. 45/04 AND THE INNOVATIONS INTRODUCED IN THE THEME OF THE PROTECTION AND PROMOTION OF HUMAN RIGHTS: REPERCUSSIONS AND ADHESION OF NEW ACTORS - Amaral, Sergio Tibiriçá; Manzan, Célia Teresinha (Seven Editora, 2025)
The text addresses the protection of human rights in Brazil, highlighting the interaction between domestic and international norms, with emphasis on Constitutional Amendment 45/2004, which reinforces the effectiveness of international human rights treaties in the Brazilian legal system. DOI: https://doi.org/10.56238/sevened2024.037-134